From lobbyists to backstage diplomats:how insurers in the field of third party liability shaped nuclear diplomacy - Kyrtsis, Alexandros Andreas; Rentetzi, Maria (History and Technology, 2021)
Third party liability insurance in the event of nuclear accidents emerged as a pressing issue in the 1950s, triggered to a great extent by the activities of international organizations and major nuclear accidents. By the mid-1960s a tight international network of negotiators comprising insurers, lawyers, scientists, engineers, businessmen, and government officials made its appearance along with nuclear insurance pools. Experts, functionaries, diplomats and politicians with often diverging views and expertise were involved in negotiations over the newly emerging legal and regulatory problems related to radiation protection and third party liability in the event of severe accidents. This paper argues that insurers transformed their identities from lobbyists to backstage nuclear diplomats, making their role explicitly political and profoundly diplomatic in an emerging international nuclear order. Within this novel multilayered context of negotiations the nuclear insurance pools developed a unique form of nuclear diplomacy, altering both terms of ‘nuclear’ and ‘diplomacy’.
CRIS-Team Scopus Importer:2021-04-30
Keywords: IAEA; nuclear diplomacy; nuclear insurance pools; Third party nuclear liability